A Case of Recurrent Toxocariasis Presenting With Urticaria - Kim, Min-Hye (The Korean Academy of Asthma, Allergy and Clinical Immunology; The Korean Academy of Pediatric Allergy and Respiratory Disease, 2010)
Human toxocariasis is the most prevalent helminthiasis in Korea and other industrialized countries. The clinical features of toxocariasis are diverse, according to the involved organ. Typically, Toxocara spp. infection is easily treated with 400 mg albendazole twice a day for 5 days. However, we experienced a case of recurrent toxocariasis that was refractory to this standard therapy and presented with urticaria, an uncommon symptom in toxocariasis. A 35-year-old male visited our emergency room because of abdominal pain. He had recently consumed raw cow liver (3 weeks prior to presentation). Laboratory analyses revealed eosinophilia (1,612 cells/µL) and increased total IgE (3,060 IU/mL). Chest X-ray showed multiple lung nodules in both lungs, and computed tomography revealed multiple ground-glass opacities in both lungs and multiple tiny liver abscesses. Liver biopsy revealed an eosinophilic abscess. Enzyme-linked immunosorbent assay findings for Toxocara antigens were positive (optical density, 2.140), leading to a diagnosis of toxocariasis. We initiated a 5-day treatment with albendazole and prednisolone; however, 6 days after completing the treatment, the patient again experienced urticaria and severe itching that could not be controlled by antihistamines or hydrocortisone cream. A second bout of eosinophilia suggested recurring toxocariasis, for which we prescribed a second round of albendazole. Despite an initial improvement in his symptoms, the patient returned after 6 weeks complaining of abdominal pain for 6 hours, which was reminiscent of his first attack; he also exhibited eosinophilia. Accordingly, albendazole was administered once more for an additional 3 weeks, and his symptoms resolved.